Pengaruh Kompetensi terhadap Kinerja Karyawan CV Inaura Anugerah Jakarta - Eigis Yani Pramularso (Universitas Bina Sarana Informatika, 2018)
Abstract – Competence becomes the basic for the employee in carrying out the demands of the job that he is responsible for. Employees must continue to improve their competence so that they can adapt to change related to their field of work. In this case, the company must play a role in the development of human resources owned, especially related to the competence so that the future performance of employees will be better. The purpose of this study is to determine the effect of competence on employee performance CV Inaura Anugerah Jakarta. In this study the number of respondents are 30 employees. The data were collected using a closed questionnaire. Data analysis used normality test, linearity test, simple regression analysis, and correlation coefficient test. The results showed that competence has a positive and significant effect on employee performance CV Inaura Anugerah Jakarta. The magnitude of the correlation coefficient shows the amount of 0.396, it means the relation of competence to the employee's performance is low. Coefficient of determination or R Squared = 0.157 which means competence affect employee performance of 15.7% while the rest is influenced by other factors than competence.Key Word: Competence, Employee Performance